OUR SUCCESS IS OUR VALUES: A QUANTITATIVE STUDY ON OUR ROOT VALUES - KUVVETLİ , Murat; TAN , Ali Rıza; İNCİR, Nurettin; CEVHER, Akan; ÇOLAK , Saim (SSD Journal, 2023)
Does possessing core values lead to success? To what extent can possessing core values make us successful? To answer these questions, a study was conducted to determine whether there was an increase in the success of high school students who received core values education. The study utilized a quantitative research method with a pre-test post-test control group design. An survey was used as the data collection tool and the data was analyzed using SPSS 26. The research sample was selected using the convenience sampling method and consisted of students from Elazig Yahya Kemal Beyatli Anatolian High School. If an increase in success is observed based on the obtained data, the necessary actions will be taken to disseminate core values education by sharing the results with the school's Values Commission. If a relationship between academic achievement and core values is identified, further research can be conducted to promote the dissemination of core values education. Additionally, not only academic success, but also students' affective skills related to core values such as attitudes, beliefs, and thoughts can be measured. Future research can examine the effects of core values at different school levels and draw conclusions based on different variables.